SENYAWA GOLONGAN STEROID DARI DAUN ADAM HAWA (Rhoeo discolor (L,Her.) Hance) DAN UJI SUN PROTECTING FACTOR STEROID COMPOUND FROM ADAM HAWA (Rhoeo discolor (L,Her.) Hance) LEAVES AND SUN PROTECTING FACTOR TEST - Anggelita Anggelita; Endah Sayekti; Lia Destiarti (Tanjungpura University, 2021)
The isolation of steroid compounds from Adam Hawa leaves has been carried out through maceration, partition, separation, and purification. The relatively pure BF2 isolate was 7 mg amorphous and with a melting point of 158-1700C. Results of 1H-NMR spectrum analysis with CDCl3 solvent, 500 MHz δH: 7,53 (d, J= 5,4 Hz, = C-H ); 7,72 (d, J= 5,7 Hz, = C-H); 5,35 (1H, d, J=5,15 Hz, =C-H); 3,51 (1H, m, Ar-CH), 0,93 (d, J= 6,2 Hz, 3H), 0,86 (3H, s), 0,84 (3H, s), 0,81 (3H, m), 0,84 (d, J= 5,2 Hz, 3H). The 1H-NMR spectrum of isolate BF2 similar to the 1H-NMR spectrum of ergosterol peroxide and ergosterol. So it is predicted that BF2 isolate has resembled structures with those compounds. In vitro sunscreen tests were performed on BF2 isolates and methanol extracts using a UV-Vis spectrometer. The SPF values of BF2 isolate and methanol extract at concentrations (ppm) of 120, 140, 160 and 180 respectively were 1.913; 1,684; 2252; 2483; and also 1,428; 1,655; 2,465; 1883. The results showed that BF2 isolate and methanol extract had weak activity as sunscreen